2018
DOI: 10.1111/his.13446
|View full text |Cite
|
Sign up to set email alerts
|

Invasion in breast lesions: the role of the epithelial–stroma barrier

Abstract: Despite the significant biological, behavioural and management differences between ductal carcinoma in situ (DCIS) and invasive carcinoma of the breast, they share many morphological and molecular similarities. Differentiation of these two different lesions in breast pathological diagnosis is based typically on the presence of an intact barrier between the malignant epithelial cells and stroma; namely, the myoepithelial cell (MEC) layer and surrounding basement membrane (BM). Despite being robust diagnostic cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 48 publications
2
33
0
Order By: Relevance
“…The critical diagnostic consideration is exclusion of micro-invasive carcinoma (defined as invasive foci no larger than 1 mm; Figure 1E, 1F) admixed within the in situ tumor. Several immunohistochemical stains for myoepithelial cells can be used to assist in the clinical diagnosis of DCIS vs. invasive carcinoma, although diagnostic pitfalls exist with any one specific marker and therefore utilization of several stains is advised to most accurately assess for the presence of a myoepithelial cell layer [4]. Further, as described later in this review, decreased or variable expression of particular myoepithelial markers may in fact contribute to altered myoepithelial cell function leading to invasive progression.…”
Section: Introductionmentioning
confidence: 99%
“…The critical diagnostic consideration is exclusion of micro-invasive carcinoma (defined as invasive foci no larger than 1 mm; Figure 1E, 1F) admixed within the in situ tumor. Several immunohistochemical stains for myoepithelial cells can be used to assist in the clinical diagnosis of DCIS vs. invasive carcinoma, although diagnostic pitfalls exist with any one specific marker and therefore utilization of several stains is advised to most accurately assess for the presence of a myoepithelial cell layer [4]. Further, as described later in this review, decreased or variable expression of particular myoepithelial markers may in fact contribute to altered myoepithelial cell function leading to invasive progression.…”
Section: Introductionmentioning
confidence: 99%
“…Invasion is fundamentally defined as the breach of the basement membrane, and not just loss of myoepithelial cells. 19 While some invasive carcinomas such as well differentiated cutaneous squamous cell carcinoma and basal cell carcinomas have been reported to display a continuous basement membrane, 20 studies of breast neoplasia have repeatedly observed a gradual loss of basement membrane, as demonstrated by IHC studies, with increasing degree of tumor dedifferentiation. Thin, but often fragmented and discontinuous, basement membrane has been seen in well differentiated tumors, including tubular carcinomas, in contrast to its consistent absence of staining in poorly differentiated tumors.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with those of Moon et al (12), although the difference between the two groups in their study was smaller compared to that in our study. Patients with MTION may exhibit more edema and areolar-periareolar skin thickening because MTION involves all layers of the skin or areolar lymphatics, whereas PDB is located within the epidermis of the NAC (2,14,15).…”
Section: Discussionmentioning
confidence: 99%